Pengembangan Perangkat Pembelajaran Model Kolaboratif Jire Berbasis IT (Information and Technology) Materi Suhu dan Kalor Fisika - Nur Arny Chairunnisa; Mursalin Mursalin; Nova Elysia Ntobuo (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
Collaborative jire becomes one of the solutions that can be used as an alternative to improve learning outcomes and student cooperation. This research aims to produce the development of high school physics learning devices using it-based jire collaborative models in the form of RPP, LKPD, teaching materials and THB in temperature and heat matter. The method used is the Research and Development (R&D) research development model of Jire Collaborative. The results of the study showed: 1) Validation of learning devices reached very valid criteria; 2) The practicality of learning devices is determined through the implementation of learning reaches 87% with excellent criteria and student response questionnaire reaches 83.77% with good criteria; 3) The effectiveness of learning devices is determined through the activities of learners reaching 83.64% with good criteria and the learning outcomes of learners of temperature and heat material with a value of 0.45 with moderate N-gain criteria, Based on the results of the study concluded that the design of learning devices using the Collaborative Jire model based on IT temperature and heat material has met valid, practical, and effective criteria. Kolaboratif jire menjadi salah satu solusi yang dapat digunakan sebagai alternatif untuk meningkatkan hasil belajar dan kerja sama peserta didik.Penelitian ini bertujuan untuk menghasilkan pengembangan perangkat pembelajaran fisika SMA menggunakan model kolaboratif jire berbasis IT berupa RPP, LKPD, Bahan ajar dan THB pada materi suhu dan kalor. Metode yang digunakan adalah penelitian pengembangan Research and Development (R&D) model Kolaboratif Jire. Hasil penelitian menunjukkan : 1) Validasi perangkat pembelajaran mencapai kriteria sangat valid; 2) Kepraktisan perangkat pembelajaran ditentukan melalui keterlaksanaan pembelajaran mencapai 87% dengan kriteria sangat baik dan angket respon peserta didik mencapai 83,77% dengan kriteria baik; 3) Keefektifan perangkat pembelajaran ditentukan melalui aktivitas peserta didik mencapai 83.64% dengan kriteria baik dan hasil belajar peserta didik materi suhu dan kalor dengan nilai 0.45 dengan kriteria N-gain sedang, Berdasarkan hasil penelitian disimpulkan bahwa rancangan perangkat pembelajaran menggunakan model Kolaboratif Jire berbasis IT materi suhu dan kalor telah memenuhi kriteria valid, praktis, dan efektif.